Form and substance of identity: The reflective body - Ubalde Enríquez, Anali (2016)
No una, sino muchas muertes and Los inocentes, are two novels have in common the appearance of the teenage character in a marginal environment. In the analysis of these common elements we see the process of construction of adolescent identity, which has the feature that the bottom of identity, the most subjective and intimate subject, is determined by the shape, that would be the body teenager. Therefore, we tested the concept of reflective body, as the body that being outside and being under the gaze of others, generates the necessary reflection so that there is a predominance of the subject on the community.